2017
DOI: 10.1016/j.ijdevneu.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Morphine exposure and maternal deprivation during the early postnatal period alter neuromotor development and nerve growth factor levels

Abstract: The objective of this study was to verify whether repeated morphine administration and maternal deprivation in early life alter neurobehavioral development and central nerve growth factor (NGF) levels. A total of 58 male Wistar rat pups were used in our study. From postnatal day 1 (P1), litters were daily deprived of their mother for 3h; this was continued for the first 10days of life. Animals were divided into 5 groups: total control (C), did not receive any intervention; saline (S), received saline solution;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Briefly, pups were placed in a supine position and their latency time to turn over their longitudinal axis to restore a normal prone position was measured. Such a task was considered to be fully achieved when the pups turned of 180° around their longitudinal axis and when their four paws were in contact with the plane surface within the observed 120‐s timeframe (Karalis et al, 2011; de Oliveira et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, pups were placed in a supine position and their latency time to turn over their longitudinal axis to restore a normal prone position was measured. Such a task was considered to be fully achieved when the pups turned of 180° around their longitudinal axis and when their four paws were in contact with the plane surface within the observed 120‐s timeframe (Karalis et al, 2011; de Oliveira et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The latency time tobothturn aroundof 180° to face upwards and climb up the board with their forepaws reaching the upper edge of the board was measured. Finally, thetest results were considered to be negative when the pups did not succeed in such a task within 120 s (Horvath et al, 2013; de Oliveira et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have revealed that opioid exposure during pregnancy in rodents leads to changes in BDNF and NGF levels in the brain of offspring, and thus, neurobehavioral defects (Ahmadalipour, Ghodrati‐Jaldbakhan, Samaei, & Rashidy‐Pour, 2018; Oliveira et al, 2017; Wu et al, 2014; Wu, Mo, Yabe, Schwartz, & Robinson, 2001).…”
Section: Introductionmentioning
confidence: 99%